1992
DOI: 10.1002/j.2161-4296.1992.tb01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Multipath Effects on GPS Code Phase Measurements

Abstract: An analysis of multipath errors in GPS code phase measurements is presented, assuming the code phase is measured with the widely used noncoherent delay lock loop. Both specular and diffuse reflections are considered. A rough estimate for the fading bandwidth is given for mobile and stationary users, showing that averaging is far more effective for mobile than for stationary users. In general, however, a certain mean range error is present for both stationary and mobile users, depending on the power‐delay profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…A noncoherent DLL (NCDLL) purposefully performs nonlinear operations to ensure robustness against phase uncertainty in the received signal and thus is widely used in GPS receiver-tracking schemes. It has been shown in the literature (Van Nee 1991, 1993, 1995 that this nonlinearity leads to a measurement bias in cases where signals are corrupted by high-frequency fading multipath such that the composite signal cannot be perfectly tracked by the receiver. The goal of the tracking process in the DLL is to maintain synchronization between the incoming GPS transmission and a locally generated replica of that signal so that an estimate of signal propagation time can be made.…”
Section: Fast Fading Multipath Model Theorymentioning
confidence: 98%
See 2 more Smart Citations
“…A noncoherent DLL (NCDLL) purposefully performs nonlinear operations to ensure robustness against phase uncertainty in the received signal and thus is widely used in GPS receiver-tracking schemes. It has been shown in the literature (Van Nee 1991, 1993, 1995 that this nonlinearity leads to a measurement bias in cases where signals are corrupted by high-frequency fading multipath such that the composite signal cannot be perfectly tracked by the receiver. The goal of the tracking process in the DLL is to maintain synchronization between the incoming GPS transmission and a locally generated replica of that signal so that an estimate of signal propagation time can be made.…”
Section: Fast Fading Multipath Model Theorymentioning
confidence: 98%
“…This paper concerns itself specifically with the latter since an abundance of theory and validation data (Braasch 1992;Cox et al 1999;Braasch and DiBenedetto 2001) has been produced for the static and low-dynamics cases. Work in the analysis of highdynamic multipath has produced mathematical descriptions of discriminator functions for general cases of multipath-corrupted signals in coherent and noncoherent delay lock loops (Van Nee 1991, 1993, 1995.…”
Section: Fast Fading Multipath Model Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The = k 3 I e − I l I e + I l (3) tracking loops accurately follow satellite-user dynamics, atmospheric and clock effects. However, in the presence of a secondary signal, these loops…”
Section: Introduction 2 Tracking Loopsmentioning
confidence: 99%
“…However, the variability of the ionospheric conditions may create additional range biases when smoothing. Van Nee in [19] showed that due to the non-zero mean of code-phase multipath, multipath effects cannot be eliminated by simply averaging over longer periods.…”
Section: Overview Of Multipath Related Studies In Gnssmentioning
confidence: 99%